Changing Patterns of Reye's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Trends in the clinical pattern of Reye's syndrome in the British Isles between 1982 and 1990, and their relation to the June 1986 warnings against the use of aspirin in children, were analysed at the PHLS Communicable Disease Surveillance Centre, London, and other Centres in the UK.